Video Game Success Using D&M among Batam Consumers - Tony Wibowo; El Vin Ho (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
This study aims to understand how to answer the success of video games on user satisfaction and use the research method DeLone and McLean Information Systems Succes Model on quantitative research. And it can be useful for the public to add new insights and for game developers to know the factors that influence user satisfaction in determining the success of online video games. The variables in this study are Perceived Enjoyment, Perceived ease of use, Perceived System quality, Perceived Service Quality, Satisfaction, and Continuance intention and population in Batam community, analysis using SPSS and AMOS. This research implies that game developers need to pay attention to and improve the quality of services provided to users to increase user satisfaction.